SAVUNMA SANAYİİNDE KULLANILAN CUZN10/CUZN30 PİRİNÇ ALAŞIMLARINA UYGULANAN FARKLI ISIL İŞLEM PARAMETRELERİNİN DERİN ÇEKİLEBİLİRLİĞE ETKİSİ - BÖLÜKBAŞ, DOĞAN (Fırat Üniveristesi, 2024)
Bu tez çalışmasının amacı, Savunma Sanayiinde kullanılan CuZn30 kovan yüksük ve CuZn10 mermi yüksük pirinç alaşımların üretiminde karşılaşılan kopma ve çatlama sorunlarını gidermek için farklı ısıl işlem parametreleri uygulanarak üretilen ürünlerin mekanik ve mikro karakteristik yapısını incelemek ve optimum tavlama parametrelerini kararlaştırmaktır. Farklı parametreler uygulanarak elde edilen CuZn30 kovan yüksük ve CuZn10 mermi yüksük pirinç alaşımlı ürünlerin mikroyapı ve mekanik özelliklerine etkisi incelenmiştir. Üretilen numunelerin mikroyapı özelliklerini belirlemek mekanik özelliklerini belirlemek amacıyla; tane boyutu analizleri ve mikrosertlik testleri yapılmıştır. Sonuç olarak CuZn10 (MS90) numunelerine uygulanan derin çekme işlemlerinde en uygun ısıl işlem prosesi 650°C 1 saat olarak belirlenmiştir, CuZn30 (MS70) numunelerine uygulanan derin çekme işlemlerinde en uygun ısıl işlem prosesi 670°C 1 saat olarak belirlenmiştir.

The aim of this thesis study is to examine the mechanical and micro characteristic structure of the products produced by applying different heat treatment parameters in order to eliminate the rupture and cracking problems encountered in the production of CuZn30 shell ferrule and CuZn10 bullet ferrule brass alloys used in the defense industry and to decide the optimum annealing parameters. The effects of CuZn30 barrel ferrule and CuZn10 bullet ferrule brass alloy products obtained by applying different parameters on the microstructure and mechanical properties were examined. In order to determine the microstructural properties of the produced samples and their mechanical properties; Grain size analyzes and microhardness tests were performed. As a result, the most suitable heat treatment process in the deep drawing processes applied to CuZn10 (MS90) samples was determined as 650°C for 1 hour, and the most suitable heat treatment process in the deep drawing processes applied to CuZn30 (MS70) samples was determined as 670°C for 1 hour.
The effect of different heat treatment parameters applied to Cuzn10/Cuzn30 brass alloys used in the defense industry on deep drawbility
Keywords: Metalurji Mühendisliği